THE EFFECT OF THE SCHMECK MODEL ON DEVELOPING AGILITY AND LEARNING THE OVERHEAD SETTING SKILL IN VOLLEYBALL - Al-Bazi, Asawar Jamal Jalil; Al-Zubaidi, Amer Rashid Shiyal (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. Learning, in its fundamental concept, relies on the individual’s capability, readiness, and the amount of time needed by the learner. The learner represents the core of the educational process, and the primary objective of this process is to enhance the learner’s physical and skill-related abilities. Objectives. The study aimed to identify the effect of the Schmeck model on developing agility and learning the overhead setting skill in volleyball for both the experimental and control groups, as well as to determine the superiority of the Schmeck model in enhancing agility and learning the overhead setting skill between the two groups. Method. The experimental method was employed using the design of equivalent groups, as it was deemed suitable for addressing the research problem. The research population consisted of second-year students at the College of Physical Education, with a total of (206) students. A random selection method was used to ensure that each individual had an equal chance of being chosen for either group. The experimental group received instructional units based on the Schmeck model, while the control group followed the curriculum adopted by the course instructor. The instructional program consisted of (8) teaching units delivered at a rate of two sessions per week. The researchers utilized the Statistical Package for the Social Sciences (SPSS) to process and analyze the data. Results. The most significant conclusions reached by the researchers were that the Schmeck model achieved a notable improvement in developing agility and a clear advancement in the technical performance of the overhead setting skill in volleyball for both the experimental and control groups. Conclusion. Furthermore, the experimental group outperformed the control group in the post-tests. The recommendations emphasized the necessity of adopting the Schmeck model, as it contributes to enhancing agility and developing the technical performance of the overhead setting skill. Additionally, the study recommended conducting similar research addressing the Schmeck model in relation to other volleyball skills.